2012
DOI: 10.5897/ajb12.233
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Meloidogyne incognita by Trichoderma harzianum and Serratia marcescens and their related enzymatic changes in tomato roots

Abstract: Biological control against the root-knot nematode, Meloidogyne incognita was proven to occur in tomato, Solanum lycopersicom, soil-drenched with different isolates of Trichoderma harzianum and a commercial suspension of Serratia marcescens (Nemaless). The potential of such biocontrol agents to trigger plant defense response was discussed. Nematode reproduction in the presence of such possibly induced systemic resistance (ISR) elicitors was compared with that occurring on untreated plants and treated plants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 17 publications
0
0
1
Order By: Relevance
“…Also, improvement of nematocidal effect is attributed to the increase in GLU's which is due to its ability to degrade pathogenic agent cell walls and hydrolyze the corresponding substrates (53) . In contrast, this result disagrees with Abd-Elgawad et al (54) , who found nematode infection had no effect on GLU activity but increased PPO activity in inoculated roots compared to uninoculated roots. By comparing the e ciency of soil drench and root dipping experiments as an approach to applying biocontrol, soil drench is preferable, and that can be explained by the higher effective performance of optimised bacterial cells than in the case of root dipping.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, improvement of nematocidal effect is attributed to the increase in GLU's which is due to its ability to degrade pathogenic agent cell walls and hydrolyze the corresponding substrates (53) . In contrast, this result disagrees with Abd-Elgawad et al (54) , who found nematode infection had no effect on GLU activity but increased PPO activity in inoculated roots compared to uninoculated roots. By comparing the e ciency of soil drench and root dipping experiments as an approach to applying biocontrol, soil drench is preferable, and that can be explained by the higher effective performance of optimised bacterial cells than in the case of root dipping.…”
Section: Discussioncontrasting
confidence: 99%